Association between neutrophilic granulocyte percentage and depression in hospitalized patients with heart failure. Issue 1 (December 2016) - Pan, Shuo; Liu, Zhong-Wei; Lv, Ying; Song, Wen-Qian; Ma, Xun; Guan, Gong-Chang; Zhang, Yong; Zhu, Shun-Ming; Liu, Fu-Qiang; Liu, Bo; Tang, Zhi-Guo; Wang, Jun-Kui
Abstract Background Previous researches reveal that depression is associated with increased inflammatory markers. As a simple and cheap inflammatory marker, we hypothesize that neutrophilic granulocyte percentage is associated with depression in hospitalized heart failure patients, whose prevalence of depression is at a very high level. Methods Three hundred sixty-six cases of hospitalized heart failure patients with left ventricular ejection fraction (LVEF) ≤45% and New York Heart Association (NYHA) class II-IV were enrolled. All the enrolled patients received Hamilton Rating Scale for Depression (24-items) (HAM-D24 ). The demographic, clinical data, blood samples and echocardiography were documented. The Pearson simple linear correlation was performed to evaluate the confounding factors correlated with HAM-D24 depression index. The significantly correlated factors were enrolled as independent variables in Logistic regression to determine the risk or protective factors for depression, which was taken as dependent variable. Results Two hundred ten cases of hospitalized heart failure patients (57.4%) had depression. Among them, 134 patients (63.8%) had mild depression, 58 patients (27.6%) had moderate depression and 18 patients (8.6%) had severe depression. Pearson simple linear correlation revealed that in hospitalized patients with heart failure, the neutrophils granulocyte percentage was positively correlated with the HAM-D24 depression index (r  = .435, p  < .001). After the adjustment of age, BMI, number of members of the household, smoking index, New York Heart Association (NYHA) classification, hemoglobin, TC, LDL-C, creatinine, cystatin-C, TBIL and albumin, the neutrophils granulocyte percentage is still significantly associated with depression in hospitalized heart failure patients (OR  = 1.046, p  < .001). Conclusions The neutrophils granulocyte percentage may be used as a new marker for depression in hospitalized heart failure patients.